2017
DOI: 10.1007/s00404-017-4596-1
|View full text |Cite
|
Sign up to set email alerts
|

Hyperandrogenemia and ovarian reserve in patients with Mayer–Rokitansky–Küster–Hauser syndrome type 1 and 2: potential influences on ovarian stimulation

Abstract: The rate of hyperandrogenemia was significantly higher in MRKH patients compared to healthy age-matched controls. Though, ovarian reserve (AMH level) was not reduced compared to controls. Future studies are needed to identify optimal ovarian stimulation protocols as well as to implement a systematic multicenter reporting system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 37 publications
1
8
0
8
Order By: Relevance
“…Other relevant laboratory tests include FSH, LH, androgens and estradiol, which are generally considered to be normal in MRKH syndrome [3,83]. However, biochemical (non-clinical) hyperandrogenemia was recently reported in~50% of patients [84], but this finding requires further validation. Uterus agenesis/aplasia in MRKH syndrome has two phenotypic presentations.…”
Section: Clinical Presentation Diagnosis and Associated Malformationsmentioning
confidence: 99%
“…Other relevant laboratory tests include FSH, LH, androgens and estradiol, which are generally considered to be normal in MRKH syndrome [3,83]. However, biochemical (non-clinical) hyperandrogenemia was recently reported in~50% of patients [84], but this finding requires further validation. Uterus agenesis/aplasia in MRKH syndrome has two phenotypic presentations.…”
Section: Clinical Presentation Diagnosis and Associated Malformationsmentioning
confidence: 99%
“…Indeed, the use of oral contraceptives with antiandrogenic potential, such as cyproterone acetate with ethinyl estradiol, is suggested by the European S1 guideline for HS for female patients with menstrual abnormalities, signs of hyperandrogenism, or upper normal or increased serum levels of DHEA, androstenedione, and/or SHBG [19]. As regards the MRKH syndrome, Henes et al [20] reported that the proportion of hyperandrogenemia without clinical symptoms was significantly high in MRKH syndrome patients when compared to age-matched controls. Herein, we reported the case of a Caucasian female affected by MRKH syndrome which developed for the first time HS manifestations after starting an ovarian stimulation to perform IVF.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…They have spontaneous ovulation and normal ovarian reserve. 17 Ovarian anomalies are rare, and include unilateral agenesis, ectopic location, polycystic or streak morphology. The ovaries are occasionally displaced cranially and laterally to the external iliac arteries, 2,6 though most reported oocyte retrievals are performed transvaginally.…”
Section: Creation Of the Neovaginamentioning
confidence: 99%